The Moderating Role of Anxiety in the Relationship between Personality Traits and Coping Strategies among Female Students - Maryam Tehranizadeh; Roghieh Haji-Rostamloo (Shahid Beheshti University of Medical Sciences, 2018)
Background and Objective: The relationship between personality characters and coping strategy has been shown in various studies. However, there is little knowledge about the variables that may affect this relationship in girls. Which have the negative effects on their behavior, when using coping strategies? The aim of study determines the role of moderating anxiety in relation personality traits and coping styles in female students. Materials and Methods: This study was descriptive and correlation and conducted the participation of 221 students of Payame Noor University in the academic year 2015-2016. The sampling method was available and the data were collected using coping strategies, state- trait anxiety and NEO-FFI Big five factor Personality questionnaires. Data were analyzed based on Pearson correlation and multiple regressions and using 21 version of SPSS software. Results: The mean (SD) age of participants was 25.3 (2.7) and in they were of the middle socioeconomic class. The adjusted strategy score with the mean (SD) 140.9 (17.1) had a negative correlation with anxiety score with the mean (SD) 35.9 (4.6): r=-0.294, P<0.05 which meant that the anxiety score increased with decreased adjusted strategy score. The isolation score with the mean (SD) 28.2 (9.5) had a positive correlation with anxiety score: r=0.546, P<0.05. There was a significant and positive relation with maladjusted strategy 64.7 (10), (P<0.05). There was a direct moderate correlation between anxiety (r=0.245) and neuroticism (r=0.341) with maladjusted strategy with the mean (SD) 64.7(10). Conclusion: The study showed that there was a positive correlation between maladjusted strategy and neuroticism and that anxiety can reinforce the relationship between neuroticism and maladjusted strategy.